2011
DOI: 10.1063/1.3629784
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure basis for strong piezoelectricity in Pb-free Ba(Zr0.2Ti0.8)O3-(Ba0.7Ca0.3)TiO3 ceramics

Abstract: In this letter, we use transmission electron microscopy to study the microstructure feature of recently reported Pb-free piezoceramic Ba(Zr0.2Ti0.8)O3-x(Ba0.7Ca0.3)TiO3 across its piezoelectricity-optimal morphotropic phase boundary (MPB) by varying composition and temperature, respectively. The domain structure evolutions during such processes show that in MPB regime, the domains become miniaturized down to nanometer size with a domain hierarchy, which coincides with the d33-maximum region. Further convergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
133
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 251 publications
(149 citation statements)
references
References 28 publications
15
133
1
Order By: Relevance
“…The absolute values of the activation barrier W B * of about $0.75 eV are close to those of soft piezoceramic PZT-5 H at the MPB which were reported to exhibit the activation barrier W B * ¼ 0.7 eV but one order of magnitude smaller nuclei volume V* of 3 Â 10 À25 m 3 . 28 Concerning the nuclei size Gao et al 17 reported by transmission electron microscopy that the nucleating domains can hardly be seen in the pure tetragonal and rhombohedral phases of BCZT100x, because in these phases, the critical nuclei rapidly develop to their equilibrium domain size which is in the micrometer range. In the phase transition region near the MPB, they report nanodomain features of 20 nm to 100 nm, which are in agreement with our reported V* values of about 2 to 3 Â 10 À24 m 3 at x $0.5 in Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute values of the activation barrier W B * of about $0.75 eV are close to those of soft piezoceramic PZT-5 H at the MPB which were reported to exhibit the activation barrier W B * ¼ 0.7 eV but one order of magnitude smaller nuclei volume V* of 3 Â 10 À25 m 3 . 28 Concerning the nuclei size Gao et al 17 reported by transmission electron microscopy that the nucleating domains can hardly be seen in the pure tetragonal and rhombohedral phases of BCZT100x, because in these phases, the critical nuclei rapidly develop to their equilibrium domain size which is in the micrometer range. In the phase transition region near the MPB, they report nanodomain features of 20 nm to 100 nm, which are in agreement with our reported V* values of about 2 to 3 Â 10 À24 m 3 at x $0.5 in Fig.…”
Section: Figmentioning
confidence: 99%
“…9 At room temperature, this boundary is at x $0.5 between a rhombohedral (R) and a tetragonal (T) phase, although the exact phase diagram in BCZT100x is still controversial. 9,[12][13][14][15][16][17][18] For example, a recent study 18 suggested that an intermediate orthorhombic (O) phase and a phase convergence region where four phases (R, O, T, and cubic (C)) may occur in a narrow temperature and compositional range. Thereby, the existence of such polymorphic regions seems to be a key to achieving the outstanding piezoelectric performance.…”
mentioning
confidence: 99%
“…The high switching degree is ascribed to the high multiplicity of polarization states and considerably lower free energy anisotropy 156 , which in turn leads to a low barrier to reorient and hierarchical domain morphology. 319,347 A reduced domain size was previously shown to affect mostly irreversible switching, leading to a pronounced enhancement of this strain contribution. 227 Moreover, the soft character ( Figure 5.13 (a)) of the O phase and low thermal energy at room temperature are expected to favor irreversible switching due to the stress relief inherent to ferroelastic switching.…”
Section: 2)mentioning
confidence: 99%
“…The hierarchical domain formation was ascribed to reduced free energy anisotropy. 319 In situ temperature-dependent TEM indicated a considerable change in the hierarchical domain structure of the system. 347 Upon heating wedge-shaped domains in the O phase of BZT-0.50BCT disappeared progressively.…”
Section: Microstructurementioning
confidence: 99%
See 1 more Smart Citation